Preface: 4th International Conference on Green Environmental Materials and Food Engineering (GEMFE 2024) - Anderson, Hermosa; Li, Cunxu (Transactions on Environment, Energy and Earth Sciences, 2024)
We gratefully acknowledge the presence of all participants on the 2024 4th International Conference on Green Environmental Materials and Food Engineering (GEMFE 2024), which was successfully held during November 09-10, 2024 in Rome, Italy. GEMFE 2024 aimed to provide a platform for experts, scholars, engineers, technicians, and R&D personnel to share scientific research results and cutting-edge technologies, understand academic development trends, broaden research ideas, strengthen academic research, and promote cooperation in the industrialization of academic results.GEMFE 2024 will bring together innovative academics and industrial experts in the fields of environmental engineering, energy technology, green materials, chemical science, agricultural technology, and food engineering to a common forum. Many participants from academic, high-education institutes, and other organizations took part in the conference. The conference model was divided into two sessions, including oral presentations and keynote speeches. In the first part, some scholars, whose submissions were selected as the excellent papers, were given 10 minutes to perform their oral presentations one by one. Then in the second part, keynote speakers were each allocated 30-40 minutes to hold their speeches.I would like to express special gratitude to members of the conference committee and organizers of the conference. I would also like to thank the reviewers for their valuable time and advice which helped in improving the quality of the papers selected for presentation at the conference and for publication in the proceedings.GEMFE 2024 Conference Organizing ChairRome, Italy